Project management office typologies, types, and functions: a systematic analysis of the literature and directions for research - Monteiro, António (2024)
Project management offices (PMOs) connect the complex relationships of strategies, projects, and organizational structures to boost the success of business. However, PMOs face significant challenges in clearly defining their roles and responsibilities due to the variety of potential functions that can be assigned to them. This study presents a systematic analysis of PMO typologies, types, and respective functions, providing an in-depth understanding of the dynamic PMO role. We found 16 typologies and 60 PMO types in the literature, showing that PMOs are complex and evolving entities that can assume various forms and organizational responsibilities.